2018
DOI: 10.1007/s00414-018-1940-3
|View full text |Cite
|
Sign up to set email alerts
|

13-loci STR multiplex system for Brazilian seized samples of marijuana: individualization and origin differentiation

Abstract: It is known that Cannabis in Brazil could either originate from Paraguay or be cultivated in Brazil. While consumer markets in the North and Northeast regions are maintained by national production, the rest of the country is supplied with Cannabis from Paraguay. However, the Brazilian Federal Police (BFP) has exponentially increased the seizure number of Cannabis seeds sent by mail. For this reason, the aim of the study was to assess the 13-loci short tandem repeat (STR) multiplex system proposed by Houston et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…The PE values ranged from 0.0711 (9269) to 0.7123 (CS1), with an average value of 0.3218. In this study, CS1 was found to be the most informative maker, and similar results were observed in Houston et al (2016), Fett et al (2019), and Ribeiro et al (2020. In total, the TDP and the CPE of the 19-plex typing system were calculated to exceed 0.999 999 999 999 988 and 0.998 455 889 684 078, respectively, presenting higher efficiency than two multiplex panels containing 13-STR markers (Fett et al, 2019;Ribeiro et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The PE values ranged from 0.0711 (9269) to 0.7123 (CS1), with an average value of 0.3218. In this study, CS1 was found to be the most informative maker, and similar results were observed in Houston et al (2016), Fett et al (2019), and Ribeiro et al (2020. In total, the TDP and the CPE of the 19-plex typing system were calculated to exceed 0.999 999 999 999 988 and 0.998 455 889 684 078, respectively, presenting higher efficiency than two multiplex panels containing 13-STR markers (Fett et al, 2019;Ribeiro et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Based on previous studies and published reports, the STRs of C. sativa were selected as follows: (1) tetranucleotide and trinucleotide repeated STRs were prior to the dinucleotide-repeat STRs. The latter were excluded due to the high stutters and heterozygote imbalances ( Valverde et al, 2014b ); (2) the STRs with high probability of amplification failures were excluded ( Houston et al, 2016 ; Fett et al, 2019 ); and (3) all STRs chosen have been previously nominated using the nomenclature of International Union of Pure and Applied Chemistry (IUPAC) ( Valverde et al, 2014a , b ). In addition, one sex-determining marker and one quality control marker of C. sativa from Pei (2009) were also included in the final assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify the seized sample, a DNA extraction followed by the application of a molecular panel, developed for identification and individualization of C. sativa, was performed (Houston et al 2017). The DNeasy® Meri-con® Food Kit was used for the DNA isolation following the protocol described by Fett et al (2019). DNA amplification was performed via polymerase chain reaction (PCR) using the Multiplex PCR Kit (Qiagen, Valencia, CA, USA) according to previously described protocols (Ribeiro et al 2020).…”
Section: Dna Barcoding Assaymentioning
confidence: 99%
“…2019 13-loci STR multiplex system for individualization and origin differentiation of Brazilian seized samples of marijuana [ 716 ]; determination of Cannabinoid concentrations in 531 confiscated cannabis samples [ 717 ]; optimization of protein extraction from cannabis [ 718 ];…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%